Chatbot Efforts: Unveiling the Influence on Customer-Brand Connections - Hafsa Malik; Javaria Asim (Indus Journal of Social Sciences, 2025)
The present study researches the multifaceted dynamics of chatbot marketing initiatives concerning their influences related to quality of communication and customer-brand relationship. It also researches their impacts on loyalty response and brand advocacy within the clothing and apparel industry of Pakistan. This study adopts a quantitative approach using probability sampling. It examines communication quality and customer-brand relationship as mediators in the improvement of customer loyalty to response and advocacy, using the perspective of chatbot interactions. Data from the sample of 304 heterogeneous apparel consumers revealed significant relations among these variables of interest. Data analysis using SmartPLS 4.0 was therefore done, and from this analysis, it was realized that the chatbot marketing efforts have had positive effects on communication quality, hence enhancing the relationships between customers and the brand. These relationships drive customer loyalty, response, and brand advocacy to a significant extent, and therefore confirm that chatbots are indeed a tool for improving customer experience. Most importantly, through the proposed mediation analysis, communication quality and customer-brand relationship were identified as two imperative pathways that help retrieve more improved customer loyalty and advocacy for chatbot marketing efforts. This study contributes to chatbot marketing theory by explaining the mechanisms that drive consumer behavior in digital environments.